Manhaj al-Lugah al-‘Arabiyyah fi Madāris al-Ṡānawiyyah al-Islamiyyah: Taqwīm al-Taṭbīq Binaan ‘ala Qarar Wazīr al-Syuūn al-Dīniyyah - Muhammad Natsir; Nurkhamimi Zainuddin (ALSINATUNA, 2024)
The formulation of evaluation tools needed to apply the curriculum in the process of evaluating the application of the curriculum at the practical level in education units. The objectives of this scientific research are:  1) Describe the curriculum application evaluation model with specifications for the formulation of components, aspects, context indicators, inputs, process, product, and outputs (CIPPO). Based on the decision of the Minister of Religious Affairs No. 183, 184, 189 and the theory of linguistic performance. 2) Analyzing the evaluation results of the implementation of the Arabic language curriculum. This scientific research utilized a research and development (R&D) design) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection tools using interview, questionnaire, and documents. The data collection techniques are Dhelpi techniques; consultative discussions with experts as validators in preparing the instruments, group discussion forum; discussions with Arabic language teachers to analyze the needs and formulate the components, aspects, and indicators to achieve Arabic language curriculum application. And qualitative data analysis using triangulation method; data reduction, presentation, and conclusion. The results of the research indicated that; 1) Implementing the evaluation of the Arabic language education curriculum in the Islamic high school using the CIPPO evaluation model with representative formulas and criteria from KMA 2019 No. 183, 84, and 189 with Dell Hymess' language performance theory Furthermore, CIPPO becomes an evaluation model in the form of curriculum achievement evaluation tools that include components on; context, inputs, process, outcomes, and learning outcomes with all aspects and indicators. The results of the evaluation of the implementation of the Arabic language curriculum for Ma'arif Islamic Secondary Schools Jepara are as follows; 1) Context aspects are at a very good level. 2) Aspects of the input components of the curriculum at a good level. 3) Aspects of the process components of the curriculum at a very good level. 4) The product component aspects of the curriculum are at a good level. 5) The learning outcomes aspects of language performance are at a poor level.